Hepatosplenic sarcoidosis - Weilong Wang; Yongping Luo (Medicine, 2026)
Rationale: Sarcoidosis is a multisystem granulomatous disease that primarily affects the lungs. Isolated or concurrent hepatosplenic involvement, although not uncommon pathologically, is a rare clinical presentation that poses a significant diagnostic challenge and often mimics malignancy on imaging. Patient concerns: A 55-year-old asymptomatic female was admitted after the incidental discovery of pulmonary nodules during a health checkup. Diagnoses: Preoperative imaging, including contrast-enhanced computed tomography (CT) and fluorodeoxyglucose positron emission tomography/CT, suggested a high likelihood of splenic malignancy. A definitive diagnosis of hepatosplenic sarcoidosis was established after histopathological examination of both the resected spleen and a concurrent liver biopsy, which revealed noncaseating epithelioid cell granulomas. Interventions: The patient underwent laparoscopic splenectomy and intraoperative liver biopsy. Outcomes: The patient’s postoperative course was uneventful. Given the absence of symptoms and organ dysfunction, the patient was discharged without specific pharmacotherapy and was regularly monitored. To date, follow-up results have been unremarkable. Lessons: This case underscores that hepatosplenic sarcoidosis can mimic malignancy on advanced imaging studies, such as fluorodeoxyglucose positron emission tomography/CT. Therefore, sarcoidosis should be considered in the differential diagnosis of patients with multifocal splenic lesions and concurrent pulmonary nodules. We hypothesize that earlier incorporation of image-guided lesion biopsy into the diagnostic algorithm may improve diagnostic accuracy and avoid more aggressive surgical procedures in patients with multisystem nodular lesions.